2022
DOI: 10.3389/fsurg.2022.778303
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Synchronous Bone Metastasis in Newly Diagnosed Differentiated Thyroid Cancer: A Real-World Population-Based Study

Abstract: BackgroundClinical and sociodemographic characteristics of differentiated thyroid cancer (DTC) patients with synchronous bone metastasis (SBM) remain unclear. This real-world study aimed to elucidate the incidence and prognosis of DTC patients with SBM using population-based data.MethodsData of patients with newly diagnosed DTC from 2010 to 2016 were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Multivariable logistic regression analysis was utilized to identify predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
3
4
0
Order By: Relevance
“…In this SEER study, distant metastasis was found in 1.7% of thyroid cancer patients at the time of diagnosis, comparable to 2.03% (for PTC) as reported by Toraih et al (18) and 1.045% (for DTC) by Qi et al (6) However, an autopsy study conducted from the nationwide Duch pathology registry reported distant metastasis was present in up to 35.1% of thyroid cancer patients, and the majority of patients had more than one metastasis (19). BM occurred in 0.5% (347/ 64083) of all newly diagnosed thyroid cancer patients, which was lower than previous studies as reported ~4% (20).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this SEER study, distant metastasis was found in 1.7% of thyroid cancer patients at the time of diagnosis, comparable to 2.03% (for PTC) as reported by Toraih et al (18) and 1.045% (for DTC) by Qi et al (6) However, an autopsy study conducted from the nationwide Duch pathology registry reported distant metastasis was present in up to 35.1% of thyroid cancer patients, and the majority of patients had more than one metastasis (19). BM occurred in 0.5% (347/ 64083) of all newly diagnosed thyroid cancer patients, which was lower than previous studies as reported ~4% (20).…”
Section: Discussionsupporting
confidence: 88%
“…Preemptive surveillance for the presence of lymph node and lung metastases is the standard-of-care in thyroid cancer patients (1,2). Although thyroid cancer is predisposed to bone metastases (BM), the existent data are limited to older, retrospective, single-institution studies with small cohorts (3-5) or large cohorts but mainly focused on differentiated thyroid cancer (DTC) (6). Additionally, the occurrence of BM is less well studied, which, in the literature varies widely (7,8), occurring in 2%-15% of pooled DTC series and 1.4%-7% in papillary thyroid cancer (PTC) patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the OS of TC starts to decline steadily from age 40 [ 35 ]. A population study in Germany found that when comparing the all-cause mortality of well-differentiated TC patients with the general population, there was a moderate decline in survival in patients aged >45 years and a significant decrease in patients aged over 60 years [ 36 ]. Yang et al conducted a population-based study that evaluated and predicted the probability of death due to TC and other causes in patients with TC and found a continuous positive correlation between age and TC survival [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ho AS et al also came to the same conclusion after analyzing the TC patients and believed that the increase in age and tumour size led to a gradual increase in the mortality of non-surgical TC patients [ 26 ]. Studies have shown that thyroid cancer's overall survival (OS) begins to decline steadily from age 40 [ 27 ]. A German population-based study found a significant decrease in all-cause mortality in patients >60 years of age when DTC patients were compared with the general population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%